HCV infection in northeastern Brazil: unexpected high prevalence of genotype 3a and absence of African genotypes - PARANÁ,Raymundo (2000)
The genomic diversity of HCV embraces 6 genotypes and at least 52 subtypes with clinical and epidemiological correlations. There is a paucity of studies assessing HCV genotypes and biomolecular epidemiology in Brazil. We studied genotype distribution and epidemiological aspects in 232 HCV carriers, 133 (57,9%) males and 99 (42,1%) females, followed in the liver disease referral unit in Salvador, BA, northeastern Brazil. All of them were anti-HCV positive by 3rd generation ELISA assay, and HCV-RNA positive by RT-PCR. Genotyping was performed by INNOLIPA. Assessment of risk factors for HCV infection showed that 93 (40%) had past blood transfusion, 14 (6%) intravenous drug use, 19 (8%) inhalation of cocaine, 28 (12%) tattooing, 15 (7%) were health care workers, 5 (2%) had reused disposable syringes, 5 (2%) had multiple risk factors and in 53 (23%) no risk factor was determined. Genotype 1a was observed in 75 (32%), 1b in 72 (31%), 3a in 61 (26%), 2ab in 14 (6%); 5 (2.5%) had mixed genotypes and 5 (2.5%) were undetermined. Patients with genotype 1 had a higher mean age (P <0.05) and no particular risk factors were associated with a specific genotype. Genotype 1 largely predominates in northeast Brazil followed by genotype 3 which, in this population, does not seem to be related to intravenous drug abuse, in contrast to some European studies. Although 80% of the Salvador population comprises African-Brazilians, no African genotype was identified, which may mean that HCV was introduced into this region via European immigration. This study demonstrated some peculiarities of HCV epidemiology in Brazil and strongly suggests that HCV introduction to this region was probably related to European immigration.